Microstructure and electrical properties of in-situ annealed carbon films - Shakerzadeh, Maziar (2021)
The microstructure and electrical properties of in-situ annealed carbon films is studied in this paper. The structure of the films is studied by transmission electron microscopy, electron energy loss spectroscopy and Raman spectroscopy. The microstructure of the films strongly depends on the deposition temperature for the films deposited at high temperatures (higher than 400°C). However, at low temperatures the substrate bias is the other crucial factor which governs the microstructure of the film. Electrical conductivity of the film strongly depends on the formation of preferred orientation in the microstructure of the films.